Upper Thoracic Spine Fractures Outcomes and Complications in King Abdul-Aziz Medical City, Riyadh - Faisal Konbaz (Journal of Spine Practice)
Introduction: Upper thoracic spine fractures (T1-T6) are not uncommon. They are often high-energy injuries complicated by multiple life-threatening comorbidities. There is a controversial discussion in the literature regarding the treatment choices. Thoracic pedicle screw fixation has replaced all other fixation techniques for its success rate and safety. Despite the number of studies discussing upper thoracic spine fractures, data on literature reporting postoperative complications are deficient. The aim of the study was to assess, in a series of patients, the impact of traumatic upper thoracic fractures on sagittal alignment, the incidence of possible complications, and the effect of associated injuries.